TRADISI IKHTIFALAN DI KAMPUNG PANGGANG DESA SELAPAJANG KECAMATAN CISOKA KABUPATEN TANGERANG BANTEN(STUDY LIVING HADIS) - Ahmad Haikal; Rizki Restu Afandi; Muhammad Alif (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2024)
The Ikhtifalan tradition in Kampung Panggang, Selapajang Village, Cisoka District, Tangerang Regency, Banten, is one of the cultural activities still preserved by the local community. Ikhtifalan, held annually, primarily serves as a form of gratitude and respect for the teachings of Islam, particularly in terms of Quranic education. This event involves various segments of the community, from children to adults, featuring a variety of activities such as Quran recitation, collective prayers, and cultural celebrations. In addition to being a form of religious practice, this tradition also serves as a means of strengthening social ties among residents and maintaining community solidarity. During the event, the community gathers to share happiness and blessings, while also reminiscing about the long-standing traditions. The Ikhtifalan tradition also provides an opportunity for the younger generation to become more familiar with religious teachings through the recitation of Quranic verses. This study aims to analyze the implementation, meaning, and social impact of the Ikhtifalan tradition in Kampung Panggang, highlighting the importance of this event in strengthening social bonds, preserving cultural diversity, and maintaining local traditions amidst the rapid modernization. This activity has become an integral part of community life, reflecting the richness of culture and strong religiosity.